2019
DOI: 10.1590/0104-6632.20190362s20180151
|View full text |Cite
|
Sign up to set email alerts
|

CARBON DIOXIDE BIOFIXATION BY Chlorella sp. IN A BUBBLE COLUMN REACTOR AT DIFFERENT FLOW RATES AND CO2 CONCENTRATIONS

Abstract: CO 2 biofixation of the microalgae Chlorella sp. for different CO 2 concentrations and gas flow rates in a bubble column reactor has been investigated in this study. Microalgae were cultivated under different CO 2 concentrations (at 1.75% and 9.45% v/v) and gas flow rates (at 30, 50 and 70 ml/min). The maximum specific growth rate of Chlorella sp. was obtained for the CO 2 concentration of 1.75 % and the gas flow rate of 50 mL/min. The highest biomass productivity rate (at 0.17 g L-1 day-1) was for a sample wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Additionally, these same three metabolic processes themselves change the pH of the surrounding seawater of the algae. Therefore, these changes have serious pressure on algae, including macroalgae ( Kinnby et al, 2021 , Xiao et al, 2021 ) or microalgae ( Pourjamshidian et al, 2019 ). According to the European Water Framework Directive (EWFD) 2000/60/CE, the algal community is considered an essential indicator of anthropogenic stresses in water ecosystems since it might alter the composition of their community, leading to the change or disappearance of some species ( Baggini et al, 2014 , Elshobary et al, 2020b , Han et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these same three metabolic processes themselves change the pH of the surrounding seawater of the algae. Therefore, these changes have serious pressure on algae, including macroalgae ( Kinnby et al, 2021 , Xiao et al, 2021 ) or microalgae ( Pourjamshidian et al, 2019 ). According to the European Water Framework Directive (EWFD) 2000/60/CE, the algal community is considered an essential indicator of anthropogenic stresses in water ecosystems since it might alter the composition of their community, leading to the change or disappearance of some species ( Baggini et al, 2014 , Elshobary et al, 2020b , Han et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that with an increase in the flow rate from 50 to 70 mL/min, the maximum biomass concentration of Chlorella sp. increased from 2.5 to 2.8 g/L (Table 5) [57].…”
Section: Cyanobacterial Growthmentioning
confidence: 99%
“…Concentrations of CO 2 may be an important factor to limit growth and development of some microalgal species [28], however, minimum and maximum concentrations CO 2 dissolved in the culture medium for microalgae cultivation vary from one species to another [29]. Some microalgae can grow under atmospheric air [30], others in extremely high CO 2 concentrations ranging from 40 to 100 vol% [31]. Compressed CO 2 can also be used in cultivation [32], but this increases the costs, which are related to the capture, compression, transport or storage of this gas [33].…”
Section: Introductionmentioning
confidence: 99%